Persepsi Wali Santri Terhadap Pendidikan Seks pada Anak di TPQ Baitul Amal Kota Padang - Dewi Sarina; Ajat Hidayat; Auliya Rahmi Zen; Arsy Gusvita; Pela Safni; Thio Apri Yanda; Alfurqan Alfurqan (UIN Sunan Gunung Dajti Bandung, 2021)
This study aims to determine how the perceptions of the guardians of students regarding sex education in children. The method used in this research is a survey using a data collection instrument in the form of a questionnaire. The data obtained were then analyzed quantitatively using descriptive statistics. Respondents in this study were the guardians of twenty-three students of TPQ Baitul Amal Padang City using the purposive sampling technique. The sample is determined based on certain criteria, namely parents or guardians of students with active status at TPQ Baitul Amal. The results showed that there were twelve perceptions of TPQ Baitul Amal's guardians on sex education for children, namely 1) the importance of sex education for children 70%, 2) providing basic sex education for children 30%, 3) sex education limited to husband-wife relationships 70 %, 4) sex education is only for adults 20%, 5) guardians of students feel confused about providing sex education to children 80%, 6) guardians of students feel ashamed to deliver sex education to children 30%, 7) children will know by themselves 50 %, 8) the time is not right to provide sex education to children 30%, 9) sex education is the responsibility of teachers in schools 30%, 10) the lack of information received by guardians of students 100%, 11) children are given the freedom to seek educational information sex on the internet 30%, 12) lack of knowledge about sex education is one of the causes of sexual crimes 30%.